Modernization and dependence: An outline and critique of competing theories - Dieter Nohlen (Intereconomics, 1980)
The salient feature of the theoretical discussion of development problems is still the rivalry between two approaches. An outline and critique of the dependencia school and the modernization theory is provided in the following article which also points out possibilities of combining both these sets of explanations in an attempt to overcome the dichotomy of development theory.
Keywords: 330; Development Theory